Soil infiltration processes of different underlying surfaces in the permafrost region on the Tibetan Plateau. Issue 11 (18th August 2018) - Hu, Guo-jie; Tian, Li-ming; Zhao, Lin; Wu, Xiao-dong; Li, Ren; Wu, Tong-hua; Zhu, Xiao-fan; Du, Er-ji; Wang, Zhi-wei; Hao, Jun-ming; Li, Wang-ping; Wang, Song-he
ABSTRACT: Soil infiltration processes were evaluated under field conditions by double-ring infiltrometers with different underlying surfaces in permafrost regions of the Tibetan Plateau. The results show that initial infiltration rates, stable soil infiltration rates and cumulative soil infiltration are strongly dependent on the underlying surface types, with the highest initial and stable soil infiltration rates in the alpine desert steppe, and the lowest in alpine meadow. The effects of soil moisture and texture on infiltration processes were also assessed. Within the same underlying surfaces, the values of infiltration parameters increased with the amount of vegetation cover, while soil moisture and soil infiltration rates displayed opposing trends, with fitting slopes of −0.03 and −0.01 for the initial and stable soil infiltration rates, respectively. The accuracies of the five models in simulating soil infiltration rates and seven models in predicting cumulative infiltration rates were evaluated against data generated from field experiments at four sites. Based on a comparative analysis, the Horton model provided the most complete understanding of the underlying surface effects on soil infiltration processes. Altogether, these findings show that different underlying surfaces can alter soil infiltration processes. This study provides a useful reference for understanding the parameterization of land surface processes for simulating changes in hydrological processes under global warming conditions in the permafrost region on the Tibetan Plateau.